(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article discusses effective teaching and learning through structured lesson planning. It highlights the role of syllabi across schools, lyceums, and colleges, and examines how educators can interpret and implement syllabus objectives. The piece outlines key components of lesson planning, such as learning outcomes, teaching strategies, and assessments, emphasizing the importance of organized instruction for successful learning outcomes.